Screening and Brief Intervention for Unhealthy Drug Use: Little or No Efficacy - Saitz, Richard (Frontiers in Psychiatry, 2014)
Unhealthy drug use ranges from use that risks health harms through severe drug use disorders. This narrative review addresses whether screening and brief intervention (SBI), efficacious for risky alcohol use, has efficacy for reducing other drug use and consequences. Brief intervention among those seeking help shows some promise. Screening tools have been validated though most are neither brief nor simple enough for use in general health settings. Several randomized trials have tested the efficacy of brief intervention for unhealthy drug use identified by screening in general health settings (i.e., in people not seeking help for their drug use). Substantial evidence now suggests that efficacy is limited or non-existent. Reasons likely include a range of actual and perceived severity (or lack of severity), concomitant unhealthy alcohol use and comorbid mental health conditions, and the wide range of types of unhealthy drug use (e.g., from marijuana, to prescription drugs, to heroin). Although brief intervention may have some efficacy for unhealthy drug users seeking help, the model of SBI that has effects in primary care settings on risky alcohol use may not be efficacious for other drug use.